Rattle of a simple man - Dyer, Charles 1928-2021 (Studiocanal, 2023)
"Rattle of a simple man (1964) directed by Muriel Box, follows Percy Winthram (Harry H Corbett), a shy, naïve 39-year-old who is in London with his friends for the Cup Final. When he meets beautiful hostess Cyrenne (Diane Cilento) in a Soho strip club and accepts a bet, a night of lust seems to be on the cards, but back at her apartment Percy's innocence and vulnerability become all too evident."
Bildformat: 1.66:1
Extras: "Game for anything: Muriel Box & Rattle of a simple man", Interview mit Hugh Futcher, "Behind the scenes stills gallery"
Original 1964
Keywords: Film; DVD-Video